2020
DOI: 10.1017/s0007123420000058
|View full text |Cite
|
Sign up to set email alerts
|

Do as I Say or Do as I Do? How Social Relationships Shape the Impact of Descriptive and Injunctive Norms of Voting

Abstract: Social norms play an important role in our understanding of why people vote, yet very little is known about the relative importance of descriptive and injunctive norms for voter turnout or how normative influence is affected by the political and social relationship between citizens. Using political discussion network data from the British Election Study, this article examines the joint effect of descriptive and injunctive norms on turnout. It demonstrates that citizens follow the example of those closest to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…We control for the social class of the discussant, and the frequency of dyadic political discussion because we might expect that respondents would be more likely to pick up messages about approval and disapproval the more often they discuss politics together. We also include controls for dyadic social relationship as it has previously been shown that social pressures from close family members tend to be most influential (Blais et al 2019;Fieldhouse and Cutts 2020). This finding is repeated in our data as shown in Fig.…”
Section: Injunctive Norms and Shared Partisanshipmentioning
confidence: 55%
See 3 more Smart Citations
“…We control for the social class of the discussant, and the frequency of dyadic political discussion because we might expect that respondents would be more likely to pick up messages about approval and disapproval the more often they discuss politics together. We also include controls for dyadic social relationship as it has previously been shown that social pressures from close family members tend to be most influential (Blais et al 2019;Fieldhouse and Cutts 2020). This finding is repeated in our data as shown in Fig.…”
Section: Injunctive Norms and Shared Partisanshipmentioning
confidence: 55%
“…That is, the coefficients for both opposing and shared identification are different to the reference category, but comparing their respective effect sizes and credible intervals, the latter are more likely to be perceived to approve of the respondent voting than the former. The effects are as large, or larger than, the equivalent effects for social relationship, which appear to be a function of social distance (Blais et al 2019;Fieldhouse and Cutts 2020). Spouses and partners have a greater effect on respondents' perceptions of discussant approval of voting than other family members, which in turn matter more than friends do and so on.…”
Section: Injunctive Norms and Shared Partisanshipmentioning
confidence: 81%
See 2 more Smart Citations
“…We first consider norms, defined here as “rules and standards that are understood by members of a group, and that guide and/or constrain social behavior without the force of law” (Cialdini & Trost, 1998, p. 152). The relevance of social interactions, normative standards, and trust in forming actions and behaviors has been stressed in the literature (Uslaner, 2000; Bicchieri, 2005; Rothstein & Uslaner, 2005; Hoffman, 2007; Fieldhouse & Cutts, 2021; Fieldhouse et al., 2022). In particular, giving is likely to be influenced by personal psychology but also by the behavior of the subject's reference group, a point related to the concept of descriptive norms, i.e., what is (perceived to be) “normal” or what most people do in a particular context (Cialdini et al., 1990).…”
Section: Explaining the Act Of Giving: The Debate In The Literaturementioning
confidence: 99%